2018
DOI: 10.3233/jad-170667
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exergaming in People with Dementia: Results of a Systematic Literature Review

Abstract: Background:Physical exercise benefits functioning, health, and well-being. However, people living with dementia in particular hardly engage in exercise. Exergaming (exercise and gaming) is an innovative, fun, and relatively safe way of exercising in a virtual reality or gaming environment. It may help people living with dementia overcome barriers they can experience regarding regular exercise activities.Objective:This systematic literature review aims to provide an overview of the cost-effectiveness of exergam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 53 publications
1
67
1
2
Order By: Relevance
“…The group model used here provides opportunities for social interaction, and the experience of conducting the study in day programs as part of their regular activity schedule demonstrates the potential for implementation. This is one of the first studies examining the use of MBTs by PCI for leisure activities and further investigation of the impacts (e.g., psychosocial, cognitive, and physical) is indicated [26].…”
Section: Discussionmentioning
confidence: 99%
“…The group model used here provides opportunities for social interaction, and the experience of conducting the study in day programs as part of their regular activity schedule demonstrates the potential for implementation. This is one of the first studies examining the use of MBTs by PCI for leisure activities and further investigation of the impacts (e.g., psychosocial, cognitive, and physical) is indicated [26].…”
Section: Discussionmentioning
confidence: 99%
“…This author then screened titles and abstracts for eligibility. All the references of the review papers [11][12][13][14][15][16][18][19][20][22][23][24][25]27,28 were manually searched. A full-text version was obtained for studies that met the inclusion criteria based on their abstract.…”
Section: Data Extractionmentioning
confidence: 99%
“…Perhaps the most well-known application of virtual reality in this setting is as a tool to enhance clinicians’ and carers’ understanding and attitudes towards the experiences of PLWD through enabling them to experience what it is like to live with dementia [10, 16]. Recently, virtual and augmented reality for PLWD has been under investigation as a cognitive assessment and diagnostic tool and in the promotion of physical activity [10, 17] and fall prevention [18, 19]. In 2015, a study by García-Betances et al [10] indicated that virtual and augmented reality technology interventions for PLWD lacked high levels of immersion and interaction and that future virtual reality environments should be tailored to the needs of PLWD and their symptoms.…”
Section: Introductionmentioning
confidence: 99%